Reversibility of Acquired Amyloid Polyneuropathy After Liver Retransplantation. Issue 10 (5th August 2013) - Antonini, T. M.; Lozeron, P.; Lacroix, C.; Mincheva, Z.; Durrbach, A.; Slama, M.; Vibert, E.; Samuel, D.; Adams, D.
Abstract Domino liver transplantation (DLT) has become an accepted procedure designed to address problems with organ limited supply. However, cases of acquired amyloid neuropathy are increasingly being recognized following this procedure. Until now, only one patient had undergone liver retransplantation and follow‐up findings were not reported. We describe the case of a 72‐year‐old patient with partial recovery from acquired amyloid neuropathy following retransplantation with a deceased donor 7 years after DLT performed for end‐stage liver disease. His clinical and paraclinical improvement is described, and the impact of this case on the indication for a domino procedure and the challenges linked to retransplantation are discussed.